CHARACTERISTICS OF MAIN DRUG THERAPY TYPES IN SUBJECTS WITH ATRIAL FIBRILLATION IN POPULATION - S. K. Malyutina; М. Yu. Shapkina; A. N. Ryabikov; E. V. Mazdorova; Е. М. Avdeeva; L. V. Shcherbakova; M. Bobak; J. A. Hubacek; Yu. P. Nikitin (Кардиоваскулярная терапия и профилактика, 2018)
Nowadays atrial fibrillation (AF) retains its leading position among arrhythmias in the world. Despite significant progress in treatment, this rhythm disturbance remains one of the leading causes of stroke (Str) and heart failure. Obviously, more action is needed on the ascertainment and the quality control of treatment of AF.Aim. To assess the frequency and main groups of drug therapy in patients with AF in the Russian population sample of middle, elderly and senile age in cross-sectional study, 2015-2016.Material and methods. The random urban population sample of men and women of 58-82 y.o. (n=2339) was examined in 2015-2016 in Novosibirsk. The entire subsample with AF included 76 people (3,2%). The presence of AF was defined by ECG with Minnesota coding. Cardiovascular diseases and their risk factors were assessed by standard epidemiological methods. We took into account the regular intake of drugs during the last two weeks, followed by coding with Anatomical therapeutic chemical classification system. ANOVA and nonparametric statistical methods were used.Results. In studied entire subsample of subjects with AF aged 58-82 y.o., the average CHA2DS2VASc estimate of Str risk was of 4,7 in women and of 3,2 in men. Those with AF received beta-blockers (BB) in 43,4% of, angiotensin-converting-enzyme inhibitors (ACEi) — in 38,2%, cardiac glycosides — in 25,0%, anti-atherosclerotic drugs — about 33% and antidiabetic — 14,5%. Anticoagulants and antiplatelet were received in 42,1%, the aspirin was most frequent (25%), direct inhibitors of thrombin (NOAC) were received in 4% of subjects with AF. About 16% were in a drug-free state. Overall, the frequency of the medication taking of the drug treatment groups analyzed in the population sample was higher in women than in men.Conclusion. In 2015-2016, the general spectrum of drug treatment in subjects with AF in Russian population sample aged 58-82 was in line with the recommended standards for AF treatment, but the coverage of treatment with main drug classes is insufficient (about 40%). The most common were BB, ACEi, lipid-lowering drugs, aspirin and digoxin. Every 4th subject with AF took an aspirin for the prevention of thromboembolism, and only 4% received NOAC.